Spanish null complement anaphora at the grammar-discourse interface - Iker Zulaica-Hernández (Quaderns de Filologia: Estudis Lingüístics, 2018)
The study of null complement anaphora (NCA) is important for the grammar-discourse interface as it seems to incarnate some of the core processes commonly found in other discourse phenomena, namely: reference, anaphora, ellipsis, inference, salience, or accommodation. Although NCA has been studied extensively, the debate whether it is an elliptical or an anaphoric process is still ongoing. This paper contributes to the view of NCA as a deep anaphor by providing evidence from Spanish discourse. I argue that NCA is an anaphor that selects the most prominent antecedent in well-defined discourse hierarchical structures. My analysis is mainly based on the comparison among Spanish neuter pronouns and NCA, and on the observed similar behavior shown by NCA and pronouns under discourse embedding conditions. Previous accounts on NCA are reviewed (Depiante 2000, 2001; Williamson 2012), and a tentative analysis of VP ellipsis based on discourse relations (Hardt & Romero 2004) is applied to Spanish NCA.